Turning a Liability into an Asset: How the Challenge of Powering Indonesia’s Remote Grids is an Opportunity to Shape Cutting-Edge Energy Policy - Guild, James (Indonesian Journal of Energy, 2019)
President Jokowi has promised to add 35 GW of power to the national grid, while the Ministry of Energy and Mineral Resources wants to source 23% of its power from renewable sources by 2025. It will be difficult to reconcile these two goals as the majority of Indonesia’s 35 GW is expected to come from high-capacity coal and gas-fired plants on Java and Sumatra. This runs the risk of both undershooting the renewables goal and neglecting the more remote provinces in eastern Indonesia that rely mainly on imported diesel fuel. With a shrewd policy aproach, this could pose an opportunity to begin developing small-scale renewable power sources – such as solar, wind, and biomass gasification – in more remote parts of Indonesia where natural resources are plentiful and large-scale fossil fuel plants are impractical. This would allow PLN to both boost the share of renewables in the energy mix and acquire experience running flexible micro-grids capable of managing diverse and decentralized energy sources. This would put Indonesia ahead of the curve, as efficient grids that can draw power from a wide range of sources will likely play a big role in the future of energy policy. If PLN continues to focus narrowly on high-capacity gas and coal plants, it will risk getting locked into an inflexible, high-carbon structure ill-suited for the needs of the 21st century. The limits of such a model are already showing in the United States.